2004
DOI: 10.3748/wjg.v10.i1.67
|View full text |Cite
|
Sign up to set email alerts
|

Single-level dynamic spiral CT of hepatocellular carcinoma: Correlation between imaging features and density of tumor microvessels

Abstract: AIM:To investigate the correlation of enhancement features of hepatocellular carcinoma (HCC) revealed by single-level dynamic spiral CT scanning (DSCT) with tumor microvessel density (MVD), and to determine the validity of DSCT in assessing in vivo tumor angiogenic activity of HCC. METHODS:Twenty six HCC patients were diagnosed histopathologically. DSCT was performed for all patients according to standard scanning protocol. Time-density curves were generated, relevant curve parameters were measured, and gross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 32 publications
2
16
0
1
Order By: Relevance
“…CT perfusion may reflect tumor aggressiveness and therefore may allow for the prediction of prognosis based on tumor vascularity because it can provide indirect information regarding tumor neoangiogenesis. Indeed, reports relating pathologic assessments of tumor angiogenesis to CT perfusion parameters have supported the hypothesis that peak tumor enhancement and blood volume correlate most closely with the expression of vascular endothelial growth factor and microvessel density in various tumors (18,(74)(75)(76)(77).…”
Section: Assessment Of Prognosis Based On Tumor Perfusionmentioning
confidence: 95%
“…CT perfusion may reflect tumor aggressiveness and therefore may allow for the prediction of prognosis based on tumor vascularity because it can provide indirect information regarding tumor neoangiogenesis. Indeed, reports relating pathologic assessments of tumor angiogenesis to CT perfusion parameters have supported the hypothesis that peak tumor enhancement and blood volume correlate most closely with the expression of vascular endothelial growth factor and microvessel density in various tumors (18,(74)(75)(76)(77).…”
Section: Assessment Of Prognosis Based On Tumor Perfusionmentioning
confidence: 95%
“…Small and well-differentiated HCC lesions, which are often iso-or hypovascular, do not enhance and are therefore difficult to detect [85]. Enhancement on dynamic spiral CT imaging correlates with microvessel density in HCC [87]. Increase in vascularization during HCC progression results in changes in CT appearance [88].…”
Section: Imaging Of Angiogenesis In Hepatocellular Carcinomamentioning
confidence: 96%
“…MVD of tumor is a valid marker to reflect tumor angiogenesis. Chen et al [2] reported that HCC MVD can be reflected by dynamic enhancement of spiral CT scanning. MVD of tumor has been detected by marking vessel endothelium.…”
Section: Discussionmentioning
confidence: 99%